Enemy - stranger - neighbour : the image of the other in moche culture - Wołoszyn, Janusz Z., (Archaeopress pre-Columbian archaeology ;, 2021)
'Enemy - Stranger - Neighbour' is dedicated to artistic renderings of the Recuay people in Moche art, in all available and preserved media. The study offers an analysis of several dozen complex, painted and bas-relief scenes and several hundred mould-pressed, sculpted depictions of foreigners in Moche art.